2022
DOI: 10.1016/j.clml.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Differential Implications of CSF3R Mutations in t(8;21) and CEBPA Double Mutated Acute Myeloid Leukemia

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Similarly, somatic mutations clustering around the transmembrane region and intracellular domain of CSF3R have been described in the novo AML, being more frequent in AML with t(8;21)(q22;q22.1) and in AML with biallelic mutation of CEBPA . 57 , 58 , 59 The variant we found in CSF3R (c.296_299delTCTC, p.Leu99fs) causes a truncating protein at residue 103, located at the beginning of the extracellular domain. To date, it has not been demonstrated that heterozygote carriers of mutations affecting the extracellular domain of CSF3R, as could be family members of SCN patients, have an increased risk for developing AML, although the number of such patients is very low.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, somatic mutations clustering around the transmembrane region and intracellular domain of CSF3R have been described in the novo AML, being more frequent in AML with t(8;21)(q22;q22.1) and in AML with biallelic mutation of CEBPA . 57 , 58 , 59 The variant we found in CSF3R (c.296_299delTCTC, p.Leu99fs) causes a truncating protein at residue 103, located at the beginning of the extracellular domain. To date, it has not been demonstrated that heterozygote carriers of mutations affecting the extracellular domain of CSF3R, as could be family members of SCN patients, have an increased risk for developing AML, although the number of such patients is very low.…”
Section: Discussionmentioning
confidence: 85%
“…72 Later studies supported the lower frequency of CSF3R mutations in aCML (typically <10-20%, though ranging from 0 to 40% 8 ), and confirmed their high prevalence in WHO-defined CNL (80-100% of patients). 7,36,114,115 It is of note that CSF3R mutations are uncommon in acute myeloid leukemia (AML) (typically reported <3-4%) 116,117 ; however, when present, they are often associated with core-binding factor gene abnormalities and double-mutated CEBPA, the significance of which remains unclear. 118 Genotype variants may represent non-deleterious SNPs with genetic analysis of nonhematopoietic tissues confirming their germline origin.…”
Section: Csf3r Mutationsmentioning
confidence: 99%
“…65 Later studies corroborated the lower mutational frequency of CSF3R mutations in aCML, which ranges from 0% to 40%, and confirmed the high prevalence of CSF3R mutations in WHO-defined CNL (80%-100% of patients). 30,103,104 It is of note that CSF3R mutations are uncommon in AML (typically reported <3%-4%), 105,106 however, when present, they are often associated with core-binding factor gene abnormalities and double-mutated CEBPA, 107 with the significance of this association remaining unclear.…”
Section: Csf3r Mutations In Cnl: a Biological Unifying Featurementioning
confidence: 99%